Religious Reserve - Hayward, Edward F. (Harvard theological review, 1915)
Two difficulties especially beset religion as a working force among thoughtful people. One is to find an adequate terminology, which shall somewhat nearly approach in expressive power the infinitely illusive realities with which religion has to deal. The other is to guard such a terminology, when once it has been accepted, from a too literal and insistent use. Nothing is so repellent to cultivated minds, for instance, as the too frequent familiarities which men take with the name of deity. Especially is this the problem of the one who has to deal professionally with religion, and who with all his handling of divine reality must not lose that which most truly characterizes it, its reticence and reserve. It is his function to declare the being of God, and to make real to others the relations which that Being sustains toward men. All other accomplishments on his part will fail without this fundamental fitness for impressing men with a sense of some one infinitely good and enduring above the passing shows of daily living. The true minister of religion is one who has walked and talked and lived with God. Amidst human limitation and change, the fixed lights of the Spirit for him stand out clear. For him at least, intellectual doubt and moral reaction have not dimmed the eternal verities of righteousness, truth, and love. The world remains for him God's world, whatever men may have done to deteriorate it morally; and he continually seeks to renew in others a consciousness of this essential worth of life and to spur them to a greater realization of it in themselves.